Stabilization Programs and External Enforcement : Experience From the 1920's - Santaella, Julio (Washington, D.C. : International Monetary Fund, 1993)
Credibility and financing problems are important reasons why countries may seek to involve external institutions in the design and implementation of stabilization programs. In particular, governments may rely on external institutions to 'enforce' programs that would otherwise lack credibility. This paper analyzes six European currency stabilizations sponsored by the League of Nations in the 1920s. It emphasizes the means by which the League provided a 'commitment technology' and enforced compliance, thereby helping to ensure successful stabilizations. Empirical evidence indicates that countries with greater credibility problems relied more heavily on external enforcement to stabilize their currencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet